Utilization of Free Trade Agreement in Indonesia: Firm-Level Data Analysis of the Yogyakarta Special Region - Nadira Asrifa Nasution; Kiki Verico (Institute for Economic and Social Research, 2019)
This study aims to observe the utilization of Free Trade Agreement (FTA) in the Special Region of Yogyakarta. The findings are obtained by processing primary data collected from in-depth interviews and a survey of firms by applying descriptive analysis. The findings show that FTA is utilized by merely 44% of the total population of 64 firms in Yogyakarta. The benefits of FTA obtained by firms include market access, ease of processing custom documents, and lower preferential tariffs. However, the disadvantages include onerous document requirements, limited information, and difficulties in understanding regulations. Another issue related to the utilization of FTA concerns the additional provisions, such as product certificates, timeliness in obtaining COO, guidelines on information access, and registration procedures. The policy implications of the findings are discussed in conclusion.